Thermal State of the Guaymas Basin Derived From Gas Hydrate Bottom Simulating Reflections and Heat Flow Measurements. Issue 8 (26th August 2022) - Sarkar, Sudipta; Moser, Manuel; Berndt, Christian; Doll, Mechthild; Böttner, Christoph; Chi, Wu‐Cheng; Klaeschen, Dirk; Galerne, Christophe; Karstens, Jens; Geilert, Sonja; Mortera‐Gutierrez, C.; Hensen, Christian
Abstract: Seafloor heat flow provides information about the thermal evolution of the lithosphere, the magnitude and timing of volcanic activity, and hydrothermal circulation patterns. In the central Gulf of California, the Guaymas Basin is part of a young marginal spreading rift system that experiences high sedimentation (1–5 km/Myr) and widespread magmatic intrusions in the axial troughs and the off‐axis regions. Heat flow variations record magmatic and sedimentary processes affecting the thermal evolution of the basin. Here, we present new seismic evidence of a widespread bottom‐simulating reflection (BSR) in the northwestern Guaymas Basin. Using the BSR depths and thermal conductivity measurements, we determine geothermal gradient and surface heat flow variations. The BSR‐derived heat flow values are less than the conductive lithospheric heat flow predictions for mid‐oceanic ridges. They suggest that high sedimentation (0.3–1 km/Myr) suppresses the lithospheric heat flow. In the central and southeastern regions of the basin, the BSR‐derived geothermal gradient increases as the intruded magmatic units reach shallower subsurface depths. Thermal modeling shows that recent (<5, 000 years) igneous intrusions (<500 m below the seafloor) and associated fluid flow elevate the surface heat flow up to five times. BSR‐derived geothermal gradients correlate little with the depth of the shallowest magmatic emplacements to the north, where the intrusions have already cooled for some time, and the associated hydrothermal activity is about to shut down. Plain Language Summary: The mid‐ocean ridge is a seafloor volcanic system where hot magma rises and creates a new ocean floor that gradually cools down as it spreads away from the magma rising center. Sediments can bury the ocean floor, such as in the Guaymas Basin of the central Gulf of California. Heat flow measurements suggest that the accumulation of colder sediments may substantially lower seafloor temperatures below values expected for an ocean floor in an early spreading phase. These conditions are favorable for widespread methane entrapment in a solid ice‐like compound, methane hydrate. We discover methane hydrates in extensive areas of the Guaymas Basin and use them to derive subsurface temperature gradients. The thermal profile away from the seafloor‐spreading center does not decline smoothly but rather undulates. We locate the hot spots representing the areas of fluid flow triggered by recent magmatic intrusions (∼6–25 kyr) in the southern and central regions of the basin farther away from the magma rising center. The northern part of the basin is relatively colder as the adjacent continent acts as a heat sink. There, intrusions that previously fueled fluid circulation have been less active recently. Key Points: A regional bottom‐simulating reflection (BSR) in the Guaymas Basin indicates a widespread occurrence of gas hydrates The BSR derived thermal gradients show wavy patterns farther away from the spreading center, indicating strong lateral heat flow variations High sedimentation suppresses heat flow, while recent magmatic intrusion and fluid advection increase heat flow